Role of necroptosis-related genes in immune activity and prognosis of colorectal cancer - Tan, Lulu; Wang, Shuaifeng; Chang, Weilong; Zhang, Xiaoying; Deng, Rui; Yan, Huifang; Zhu, Weiwei; Wang, Huifen; Cai, Yudie; Liu, Zhibo; Tan, Yuyan; Cui, Jinyuan (Frontiers in Immunology, 2025)
BackgroundNecroptosis plays a critical role in the onset and progression of numerous malignancies, with colorectal cancer (CRC) ranking among the leading causes of cancer-related mortality worldwide. However, the relationship between necroptosis-related genes (NRGs) and CRC remains contentious. Hence, this study aims to develop a novel NRG-based signature to predict the prognosis of CRC patients and explore its potential role.MethodsTranscriptome data from the Gene Expression Omnibus (GEO) databases and the Cancer Genome Atlas (TCGA) were employed to identify cancer hallmarks associated with outcomes in CRC. A novel NRG signature was formulated and validated using least absolute shrinkage and selection operator (LASSO) regression analysis and COX regression analysis. Subsequently, univariate and multivariate Cox regression analyses, Kaplan-Meier (K-M) survival analysis, receiver operating characteristic (ROC) curves, and nomograms were utilized to assess the predictive capability of our signature. Furthermore, a variety of bioinformatics analysis algorithms were leveraged to uncover potential mechanisms, tumor immune status, and differences in drug sensitivity between the two-risk groups. The expression of signature NRGs in CRC was evaluated through quantitative reverse transcription polymerase chain reaction (qRT-PCR).ResultsA novel signature consisting of eighteen NRGs (CTSB, PAEP, ARL4C, TAP2, WFS1, BATF2, DUSP27, CXCL9, EPHB2, IRF8, CXCL13, GZMB, APOL6, NLRC5, CXCL10, IRF1, HES6, and PTGDR) was successfully established. This signature displayed consistent predictive performance and general applicability for CRC, as validated across three independent cohorts. Moreover, stromal and immune cells within the tumor microenvironment (TME) were found to be correlated with necroptosis. Additionally, notable differences in the sensitivity to anti-tumor agents were observed between the two groups. The qRT-PCR results indicated aberrant expression of these signature NRGs in CRC.ConclusionNRG was proved to be an accurate predictor of CRC prognosis. Furthermore, the novel signature exhibited consistent value and translational potential for predicting prognosis, tumor immunogenicity, and therapeutic response in CRC.